Readings in machine translation - Nirenburg, Sergei; Somers, H. L.; Wilks, Yorick, 1939- (Bradford book., 2003)
The field of machine translation (MT) -- the automation of translation between human languages -- has existed for more than fifty years. MT helped to usher in the field of computational linguistics and has influenced methods and applications in knowledge representation, information theory, and mathematical statistics. This valuable resource offers the most historically significant English-language articles on MT. The book is organized in three sections. The historical section contains articles from MT's beginnings through the late 1960s. The second section, on theoretical and methodological issues, covers sublanguage and controlled input, the role of humans in machine-aided translation, the impact of certain linguistic approaches, the transfer versus interlingua question, and the representation of meaning and knowledge. The third section, on system design, covers knowledge-based, statistical, and example-based approaches to multilevel analysis and representation, as well as computational issues.